"Listening" to Paintings: Synergetic Effect of a Cross-Modal Experience on Subjective Perception. (July 2023) - Isaacson, Atara; Assis, Amichay; Adi-Japha, Esther
This mixed-methods study focused on cross-modal change in perception of paintings, by coupling them with related musical pieces. 120 participants were assessed using an online form, distributed via social media. They were asked to choose one of three realistic or abstract paintings, evaluate their perceptual characteristics on five semantic differential rating scales and answer three questions. The participants were then given a choice of three musical pieces (pre-selected to suit each painting) to match their chosen painting. Our findings revealed a significant change in three of the five scales. Moreover, for 93 of the 120 participants, the experience of looking at a painting while listening allowed projection of newly found perception or properties associated with music (dynamism through time, mobility, and the evocation of self-expression) onto the painting. These data suggest that as observers combine stylistically-fitting music with a painting, they find new meaning and value, thereby enhancing their experience.